Among the S100 proteins, S100A12 is the most significant marker for psoriasis disease activity. (2nd September 2015) - Wilsmann‐Theis, D.; Wagenpfeil, J.; Holzinger, D.; Roth, J.; Koch, S.; Schnautz, S.; Bieber, T.; Wenzel, J.
Abstract: Background: Psoriasis is a chronic skin disease with deregulation of proteins in the immune system. These proteins include members of the heterogeneous S100 family, which have been discussed as potential biomarkers for disease severity. Objective: The aim of this study was to evaluate the impact of S100A7, S100A8, S100A9 and S100A12 as possible markers for disease activity in patients with psoriasis skin disease. Patients and Methods: S100A7, S100A8, S100A9 and S100A12 mRNA expression was determined in the skin of patients with psoriasis and controls ( N = 341) by gene expression analyses. In addition, S100 serum levels were investigated by ELISA in an independent cohort of psoriasis patients (i) untreated, with different manifestations (skin/joints), (ii) under treatment (etanercept) and (iii) healthy controls, ( N = 55). Results: All S100‐subtypes included are significantly upregulated in psoriasis skin lesions when compared with atopic dermatitis, lichen ruber and healthy donors. In untreated psoriasis patients, S100A12‐serum levels showed the closest association with disease activity (PASI) ( r = 0.542; P < 0.01). Serum levels decreased under treatment with etanercept ( P < 0.05). Conclusion: Among the investigated S100‐proteins, S100A12 showed the closest association with disease activity and therapeutic response and might therefore provide a valuable biomarker for psoriasis.